2020
DOI: 10.1021/acs.jpca.0c05688
|View full text |Cite
|
Sign up to set email alerts
|

Proton Transfer Reaction Rates in Phenol–Ammonia Cluster Cation

Abstract: Proton transfer (PT) in an interaction system of a hydroxyl–amino group (OH–NH) plays a crucial role in photoinduced DNA and enzyme damage. A phenol–ammonia cluster is a prototype of an OH–NH interaction and is sometimes used as a DNA model. In the present study, the reaction dynamics of phenol–ammonia cluster cations, [PhOH–(NH3) n ]+ (n = 1–5), following ionization of the neutral parent clusters, were investigated using a direct ab initio molecular dynamics (AIMD) method. In all clusters, PTs from PhOH+ to (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…In the present study, the intracluster reactions of O­(X)­(H 2 O) n (X = 3 P, 1 D, and 1 S, and n = 1–6), following the photoelectron detachment of a water cluster of an oxygen radical anion (O – (H 2 O) n , n = 1–6), were investigated using the direct ab initio molecular dynamics (AIMD) method. Three low-lying electronic states of oxygen atoms, O­( 3 P), O­( 1 D), and O­( 1 S), were examined. We found that the O­( 1 S)­(H 2 O) n complexes spontaneously convert into H 2 O 2 after electron detachment.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the intracluster reactions of O­(X)­(H 2 O) n (X = 3 P, 1 D, and 1 S, and n = 1–6), following the photoelectron detachment of a water cluster of an oxygen radical anion (O – (H 2 O) n , n = 1–6), were investigated using the direct ab initio molecular dynamics (AIMD) method. Three low-lying electronic states of oxygen atoms, O­( 3 P), O­( 1 D), and O­( 1 S), were examined. We found that the O­( 1 S)­(H 2 O) n complexes spontaneously convert into H 2 O 2 after electron detachment.…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia has been used as a building block for drug synthesis, allowing systematic studies of solvent-dependent photobiology through a spectroscopic understanding of its clusters. 39,40 3CI-ammonia clusters are easily accessible by laser spectroscopic techniques in the gas phase. They are of fundamental interest to chemical cluster studies, where hydrogen bondings determine the structures and functions of proteins and nucleic acids.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we employed ammonia in the 3CI‐solvent cluster system. Ammonia has been used as a building block for drug synthesis, allowing systematic studies of solvent‐dependent photobiology through a spectroscopic understanding of its clusters 39,40 . 3CI‐ammonia clusters are easily accessible by laser spectroscopic techniques in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…Proton transfer and electron transfer are two basic and extensive reactions in the chemical process. The reaction which includes transfer of both protons and electrons is called as proton-coupled electron transfer (PCET). Proton transfer reactions have undergone many experimental and theoretical studies . Previously, there have been well-reported studies on the proton transfer reaction caused by OH or NH bonds. However, the proton transfer from the relatively stable CH bonds has not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…6−9 Proton transfer reactions have undergone many experimental and theoretical studies. 10 Previously, there have been well-reported studies on the proton transfer reaction caused by OH or NH bonds. 11−14 However, the proton transfer from the relatively stable CH bonds has not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%